2016
DOI: 10.1117/1.nph.3.3.039802
|View full text |Cite
|
Sign up to set email alerts
|

Errata: Hemodynamic response to burst-suppressed and discontinuous electroencephalography activity in infants with hypoxic ischemic encephalopathy

Abstract: This paper [Neurophoton 3(3), 031408 (2016)] was originally published with redundant video still images in Figs. 10 and 11. Those videos have been incorporated into the previous Figs. 6 and 8, and Figs. 10 and 11 have been deleted. The article was corrected online on 4 May 2016. It appears correctly in print.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…In addition, it can increase the risk of self-injury, dehiscence of the surgical wound, occurrence of postoperative adverse behaviours such as intravenous catheter displacement, and can eventually be a threat to patients, parents, and primary caregivers [14] . Burst suppression is the alternation of electrical activity between isoelectric and brief bursts, often secondary to various factors, such as infantile encephalopathy, deep anaesthesia, hypoxic-ischaemic trauma, coma, and hypothermia [15] . To explore the factors associated with wake-up delirium and perioperative EEG, in a previous study, it was reported [16] that epileptiform discharges during the induction of anaesthesia are associated with wake-up delirium, which suggests that we can reduce the occurrence of epileptiform discharges by EEG monitoring during induction and further reduce the incidence of wake-up delirium.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it can increase the risk of self-injury, dehiscence of the surgical wound, occurrence of postoperative adverse behaviours such as intravenous catheter displacement, and can eventually be a threat to patients, parents, and primary caregivers [14] . Burst suppression is the alternation of electrical activity between isoelectric and brief bursts, often secondary to various factors, such as infantile encephalopathy, deep anaesthesia, hypoxic-ischaemic trauma, coma, and hypothermia [15] . To explore the factors associated with wake-up delirium and perioperative EEG, in a previous study, it was reported [16] that epileptiform discharges during the induction of anaesthesia are associated with wake-up delirium, which suggests that we can reduce the occurrence of epileptiform discharges by EEG monitoring during induction and further reduce the incidence of wake-up delirium.…”
Section: Discussionmentioning
confidence: 99%